Pengaruh Electronic Word of Mouth Terhadap Keputusan Berkunjung di Desa Wisata Cibeusi Kabupaten Subang - Nova Riana; Rieke Sri Rizki Asti Karini; Satria Delonika Regiawan (Tourism Scientific Journal, 2020)
This study aims to determine the effect of Electronic Word of Mouth on visit decision in Tourism Village Cibeusi Subang Regency. The research method used is a quantitative method with descriptive and verificative approach. The data used in this study including primary and secondary data. The samples amounted on 100 respondents, taken from the tourist population in 2018 counted as 3.218 tourists . This sample is calculated by using the Slovin formula. The sampling technique is done using incidental approach. Data collection is done using observation, questionnaire, interview and documentation. The model of the questionnaire used a Likert scale. The verificative analysis used were instrumental test (validity test and reliability test), normality test, heteroscedascity test, simple linear regression, correlation analysis, analysis of determination and partial hypothesis test. The results of this study showed that the correlation between variables categorized as moderate. The effect of the independent variable on the dependent variable was 23.7%, whilst 76.3% was influenced by other variables not examined in this study. The t test result showed that the value of  tcount  > ttable (5,512 > 1,984) with a significance of 0,000 < 0.05, so it can be concluded that the Electronic Word of Mouth has a positive and significant effect on the decision to visit Cibeusi Tourism Village, Subang Regency.